A model for mechanial peeling of dehydrated candied papaya (Carica Papaya Linn.) - Angeles, Rizza Carola R. (1984)
A model for a mechanical peeler was assembled and compared against manual peeling in terms of yield of dehydrated candied papaya. Candying was by the slow method using a 20° Brix syrup initially and stepping it up by 10° until 50°Brix. Drying in a cabinet dryer at 150°F for 4-4 1/2 hours followed. The study showed that the prototype peeler increased the percentage yield of the product by approximately 10%. Both samples were sensorially evaluated to have a moderately to slightly shrivelled appearance, a golden yellow to yellow orange color, a soft to tender but firm texture, a sweet taste, and a general acceptability rating of like moderate
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Papa; Fruit -- Preservati